THE EFFECT OF DIFFERENT NATURAL WAXES TO HYDROPHOBIC PROPERTIES OF STARCH-BASED BIODEGRADABLE FOAMS - Alexander, Ikbal; Sodri, Ahyahudin; Mizuno, Kosuke (Journal of Environmental Science and Sustainable Development, 2023)
Biodegradable foam has been vastly developed to replace polystyrene foam. However, its water absorption capacity has become a significant obstacle to being used in food packaging. Therefore, this study aims to assess the effect of incorporating natural waxes as a coating material in producing biodegradable foams. The four natural waxes are soy wax, candelilla wax, beeswax, and carnauba wax. The biodegradable foams were fabricated with cassava starch and rice straw as natural fiber sources using a thermal pressing machine. The Meyer-Rod coating method was adopted to produce high contact angle and highwater resistance starch-based biodegradable foams. Water absorption analysis was performed according to the Cobb60, and water solubility analysis was conducted based on International Standardization for Organization 10634:2018 procedure. The result shows that the surface modification of starch-based biodegradable foams with natural waxes significantly improved water absorbency and water solubility. Moreover, it is demonstrated that the use of carnauba wax had the highest decrease of Cobb60 index of 1.5 g/m2 and the lowest water solubility of 2% after carrying water for 90 min. This study concludes that the utilization of natural waxes a as a coating material for starch-based biodegradable foam could replace conventional polystyrene foam for food packaging industry.